An Exploration of Electrospun Fibers Containing Drug-Cyclodextrin Inclusion Complexes - Fatimah, Fatimah; Aytac, Zeynep; Uyar, Tamer; Pasparakis, George; Williams, Gareth R (Pharmaceutical Sciences and Research, 2020)
A series of new core-shell fibers were developed containing anticancer drugs (5-fluorouracil or ferulic acid) and their cyclodextrin inclusion complexes, with a gadolinium-based magnetic resonance imaging (MRI) contrast agent. These were prepared by electrospinning, a simple method for producing ultra-fine fibers through the application of a strong electrostatic force on a polymer solution. The shell of the fibers was formed from Eudragit S100, and the drugs were loaded in the core. Scanning electron microscopy images showed the formation of smooth ribbon-like fibers, with diameters ranging from 1.4 to 5.1 μm, and transmission electron microscopy reveals a transparent interface between the core and shell compartments. X-ray diffraction and differential scanning calorimetry data confirmed the encapsulation of the drug into the cyclodextrin cavity and the formation of amorphous solid dispersions in the fibers. Drug release from the systems at pH 1 and 7 showed that all the drug loading was released within one hour at pH 1. Based on these results, it is proposed that the relatively low molecular weight drugs were able to diffuse out of the system into the release medium at acidic pH, despite the insolubility of the shell polymer under these conditions. These findings have important implications for the design of electrospun drug delivery systems.